The Ecological Role of Type Three Secretion Systems in the Interaction of Bacteria with Fungi in Soil and Related Habitats Is Diverse and Context-Dependent - Nazir, Rashid; Mazurier, Sylvie; Yang, Pu; Lemanceau, Philippe; van Elsas, Jan Dirk (Frontiers in Microbiology, 2017)
Bacteria and fungi constitute important organisms in many ecosystems, in particular terrestrial ones. Both organismal groups contribute significantly to biogeochemical cycling processes. Ecological theory postulates that bacteria capable of receiving beneﬁts from host fungi are likely to evolve efficient association strategies. The purpose of this review is to examine the mechanisms that underpin the bacterial interactions with fungi in soil and other systems, with special focus on the type III secretion system (T3SS). Starting with a brief description of the versatility of the T3SS as an interaction system with diverse eukaryotic hosts, we subsequently examine the recent advances made in our understanding of its contribution to interactions with soil fungi. The analysis used data sets ranging from circumstantial evidence to gene-knockout-based experimental data. The initial finding that the abundance of T3SSs in microbiomes is often enhanced in fungal-affected habitats like the mycosphere and the mycorrhizosphere is now substantiated with in-depth knowledge of the specific systems involved. Different fungal-interactive bacteria, in positive or negative associations with partner fungi, harbour and express T3SSs, with different ecological outcomes. In some particular cases, bacterial T3SSs have been shown to modulate the physiology of its fungal partner, affecting its ecological characteristics and consequently shaping its own habitat. Overall, the analyses of the collective data set revealed that diverse T3SSs have assumed diverse roles in the interactions of bacteria with host fungi, as driven by ecological and evolutionary niche requirements.